Structure and Dynamics of Lanthanide Complexes of Triethylenetetramine-N,N,N',N'',N''',N'''-hexaacetic Acid (H6ttha) and of Diamides H4ttha(NHR) Derived from H6ttha as Studied by NMR, NMRD, and EPR - Zitha-Bovens, Emrin (2005)
A multinuclear NMR study on [Ln(ttha)]3- and [Ln{ttha(NHR)2}]- complexes (R=Et, CH2(CHOH)4CH2OH) shows that coordinating groups of the organic ligands in these complexes are occupying all coordination sites of the metal ions, leaving no space for coordination of H2O molecules (H6ttha=triethylenetetramine-N,N,Nprime,NPrime,Nprimeprimeprime,Nprimeprimeprime-hexaacetic acid). The lanthanides of the first half of the series bind the ttha-type ligands in a decadentate fashion, while the complexes formed with the smaller ions of the second half of the lanthanide series are nonadentate. One carboxylate group of the ligand remains unbound in the latter complexes. In principle, the ttha complexes can exist in six enantiomeric forms. Only one of the pair of diastereoisomers can interconvert without decoordination of the ligand. This pair of isomers seems to be predominant in solution. For the [Ln{ttha(NHR)2}]- complexes, the number of chiral centers is larger, resulting in 32 possible enantiomeric forms of the complexes. The NMR spectra of [Nd{ttha(NHEt)2}]- indicate that two dynamic processes occur between the isomers in solution. The NMRD curves of [Gd(ttha)]3-, [Gd{ttha(NHEt)2}]-, and [Gd{ttha(NHgluca)2}]- (NHgluca=D-glucamine) show significant differences with the previously determined outer-sphere contributions to the NMRD profiles of the corresponding [Gd{dtpa(NHR)2}]- complexes, which can be ascribed to differences in the parameters determining the electronic relaxation.